Meningioma with Metastatic Malignant Melanoma: An Unusual Coincidence - H. V. Savant; Anand Doshi; Zafar H. Sheikh; Vijay Mahajan (Indian Journal of Neurosurgery)
Simultaneous occurrence of meningioma and brain metastasis as two different histopathologically-proven lesions has been often reported in literature, however, to the best of our knowledge, contiguous occurrence of meningioma and malignant melanoma has not been reported previously in literature. A 50-year-old woman presented with features of raised intracranial pressure and left upper motor neuron signs. Imaging findings were suggestive of right frontoparietal and right parietal extra-axial space occupying extra-axial lesions. Patient underwent right frontotemporoparietal craniotomy with excision of both tumors under general anesthesia. Histopathological analysis was suggestive of transitional meningioma (World Health Organization [WHO] grade I) and malignant melanoma (WHO grade IV). Simultaneous presence of two tumors in the brain might be of the same or different histopathology. In such dual tumors, metastasis cases are varied and one source of it may be melanoma of the skin. Hence, dermatological examination can reveal the primary source of tumor in select cases.